Dyslipidemia in diffuse large B-cell lymphoma based on the genetic subtypes: a single-center study of 259 Chinese patients - Xu, Yi; Shen, Huafei; Shi, Yuanfei; Zhao, Yanchun; Zhen, Xiaolong; Sun, Jianai; Li, Xueying; Zhou, De; Yang, Chunmei; Wang, Jinhan; Huang, Xianbo; Wei, Juying; et al. (Frontiers in Oncology, 2023)
Background: Diffuse large B-cell lymphoma (DLBCL) is a kind of highly heterogeneous non-Hodgkin lymphoma both in clinical and genetic terms. DLBCL is admittedly categorized into 6 subtypes by genetics, which contains MCD, BN2, EZB, N1, ST2 and A53. Dyslipidemia is relevant to a multitude of solid tumors and has recently been reported associated with hematologic malignancies. We aim to present a retrospective study investigating dyslipidemia in DLBCL based on the molecular subtypes. Results: This study concluded 259 patients with newly diagnosed DLBCL and their biopsy specimens were available for molecular typing. Results show that the incidence of dyslipidemia (87.0%, p<0.001) is higher in the EZB subtype than in others, especially the hypertriglyceridemia (78.3%, p=0.001) in the EZB subtype. Based on the pathological gene-sequencing, patients with BCL2 gene fusion mutation are significantly correlative with hyperlipidemia (76.5%, p=0.006) and hypertriglyceridemia (88.2%, p=0.002). Nevertheless, the occurrence of dyslipidemia has no remarkable influence on prognosis. Conclusion: In summary, dyslipidemia correlates with genetic heterogeneity in DLBCL while without significant influence on survival. This research firstly connects lipids and genetic subtypes in DLBCL.